Effects of Nitrogenous Fertilization and some Insecticides on the Natural Enemies of Transgenic Bt Cotton Pests - Fadlelmawla, Mamoun; Abdelbagi, Azhari; Ishag, Abd Elaziz; Hammad, Ahmed; Hur, Jang-Hyun (EntomoBrasilis, 2021)
Field assessment of integrated management of BT cotton pests was carried out in two consecutive seasons; 2016/2017 and 2017/2018 in the experimental research farm of the Kassala University, Sudan. Four insecticides (imidacloprid, abamectin, profenofos, and lufenuron) from different chemical groups and with a different mode of action and three levels (43.81 kgha-1, 87.62 kgha-1, and 131.43 kgha-1) of soil-applied nitrogen were tested in the IPM package. Insecticides were applied at the recommended doses. A total of 7 weekly counts of prevailing natural enemies [Chrysoperla carnea (Stephens) and Aenasius bambawalei Hayat] were carried out for 4 weeks before spraying and 3 weeks post spraying starting the 3rd week from spraying. Results indicated that nitrogen level exerted no significant effects on the populations of prevailing natural enemies; C. carnea and A. bambawalei. Based on average post spray counts and percentage reduction over the control, all insecticide treatments significantly reduced the population of the natural enemies. Imidacloprid and profenofos exerted the highest reduction of C. carnea population followed by abamectin and lufenuron (56.03, 48.25, 07.78 and 06.61% respectively) in the first season, while profenofos, imidacloprid, lufenuron, and abamectin induced the highest reductions (55.94, 45.05, 17.57 and 17.33% respectively) in the second season. On the other hand, reductions in A. bambawalei population (abundant in season 1 only) followed the order; imidacloprid, lufenuron, abmectin, and profenofos (03.95, 02.63, 202.63, and 01.32%, respectively). Interactions between nitrogen fertilization and insecticide were not significant as measured by the population of prevailing natural enemies.